1987
DOI: 10.1111/j.1365-3059.1987.tb02213.x
|View full text |Cite
|
Sign up to set email alerts
|

The establishment of systemic infection in leaves of oilseed rape by Leptosphaeria maculans

Abstract: In a series of growth room experiments in which leaves of Brassica napus var. oleifera were inoculated with ascospores or pycnidiospores of Leptosphaeria maculans successful infections progressed through three consecutive phases. Initial establishment in the mesophyll was succeeded by a phase of intercellular exploration, when hyphal proliferation was highly variable and host cell necrosis always ensued, and then by a systemic phase when hyphae were consistently sparse. Host cells associated with the hyphal fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 38 publications
2
50
0
1
Order By: Relevance
“…For example an infection in autumn might cause later an infection of root collar and stem base [22]. The fungus is able to spread from the infected leaves to other parts of the plant causing the disease symptoms [23]. For this reason inhibition of the fungus on cotyledons was studied.…”
Section: Discussionmentioning
confidence: 99%
“…For example an infection in autumn might cause later an infection of root collar and stem base [22]. The fungus is able to spread from the infected leaves to other parts of the plant causing the disease symptoms [23]. For this reason inhibition of the fungus on cotyledons was studied.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work (Gladders and Musa, 1980;Hammond and Lewis, 1987) had already shown that ascospores can infect oilseed rape leaves, but these experiments now provide details of the range of conditions over which infection can occur. The experiments also suggest that the optimum temperature for infection is about 18 • C; at this temperature the shortest wetness period is needed for infection to occur.…”
Section: Discussionmentioning
confidence: 99%
“…those of Badawy et al, 1991), conidiospores have been used to inoculate leaves, which have had to be wounded beforehand because conidiospores cannot usually infect healthy leaves (Hammond and Lewis, 1987). In some experiments, leaves have been inoculated with single ascospores (Hammond and Lewis, 1987) or with ascospore suspensions (Gladders and Musa, 1980) but infection conditions were not examined. This paper describes the effects of temperature and wetness duration on infection of oilseed rape leaves by ascospores of L. maculans and the subsequent development of phoma leaf spot lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Hammond and Lewis (1987) showed that L. maculans, being a hemibiotroph, can act as a biotroph at the beginning of the infection and switch to a necrotrophic mode at the later stages of pathogenesis. However, recent works indicate that at an early stage of plant infection L. maculans can be a necrotroph, then it enters a long biotrophic stage, and finally it switches back to the necrotrophic stage (Rouxel and Balesdent 2005;Jindřichová et al 2011;Hayward et al 2012).…”
Section: Discussionmentioning
confidence: 99%